KUALITAS LAYANAN WISATA MEDIS YANG MEMPENGARUHI KEPUASAN DAN LOYALITAS WISATAWAN MANCANEGARA DI BALI - Nugraha, Yudha Eka; Paturusi, Syamsul Alam; Wijaya, Ni Made Sofia (JURNAL MASTER PARIWISATA; Volume 05, Nomor 02, Januari 2019DO - 10.24843/JUMPA.2018.v05.i02.p08, 2019)
Medical Tourism is a potential sector to develop in Bali. Medical clinics offer various medical services treatment to attract tourists. The clinics must have an excellent quality of standard services to get customers satisfaction. The aim of this study is to analyze the influence of the medical services quality on tourist satisfaction and tourist loyalty in Radiance Clinic Bali. They were about 200 respondents and selected using accidental sampling technique. The analysis uses Structural Equation Model (SEM), calculated with AMOS program. The result of research examines that service quality is a main variable with significance effects on the satisfaction and loyalty of tourists’ customers in Bali. Results of the research indicated that there is direct effect between service quality to satisfaction and satisfaction to loyalty. On the other hand, indirect effect happens between service quality to loyalty. Keywords : Service Quality, Tourist Satisfaction, Tourist Loyalty